PENGARUH BIAYA TRANSAKSI TERHADAP KEUNTUNGAN USAHATANI KEDELAI DI KABUPATEN LAMONGAN, JAWA TIMUR - Hardiyanti Sultan; Dwi Rachmina (Forum Agribisnis, 2016)
Transaction cost is one of the characteristics of imperfect market. Transaction cost on soybean farming will affect the level of profit soybean farming. The purpose of this research were to analyze the transaction cost structure and the effect of transaction cost on the profitability of soybean farming. Research method used Transaction Cost Analysis and multiple linear regression. This research was held in Lamongan, Jawa Timur and interviewed 120 soybean farmers to derive the data. The results showed that the transaction cost component on soybean farming consists of (1) information cost; (2) negotiation cost; (3) coordination cost; (4) enforcement cost; (5) monitoring cost and (6) risk cost. The amount of the transaction cost that are formed on soybean farming was Rp144.120,86. Negotiation cost was the highest cost of transaction cost component that was 60,30%, followed by information cost 14,07%, coordination cost 12,22%, enforcement cost 8,03%, monitoring cost 4,23% and risk cost 1,15%. Transacion cost have a negative and significant effect on the profitability of soybean farming.